Significance of Image Features in Camera-LiDAR Based Object Detection - Mihaly Csontho; Andras Rovid; Zsolt Szalay (IEEE Access, 2022)
In autonomous cars accurate and reliable detection of objects in the proximity of the vehicle is necessary in order to perform further safety critical actions which depend upon it. Many detectors have been developed in the last few years, but there is still demand for more reliable and more robust detectors. Some detectors rely on a single sensor, while some others are based upon fusion of data from multiple sources. The main aim of this paper is to show how image features can contribute to performance improvement of detectors which rely on pointcloud data only. In addition it will be shown, how lidar reflectance data can be substituted by low level image features without degrading the performance of detectors. Three different approaches are proposed to fuse image features with point cloud data. The extended networks are compared with the original network and tested on a well-known dataset and on our own data, as well. This might be important when the same pretrained model is to be used on data generated by a lidar using different reflectance encoding schemes and when due to the lack of training data retraining is not possible. Different augmentation techniques have been proposed and tested on the KITTI dataset as well as on data acquired by a different lidar sensor. The networks augmented with image features achieved a recall increase of a few percent for occluded objects.